IMPACT OF ALUMINIUM TANNING ON THE INTERNAL MEMBRANE OF BOVINE STOMACH FOR NOVELTY LEATHER (Biological Sciences - PJSIR, 2001)
Internal membrane of bovine stomach is a by-product of slaughter house. Employing masked alum tannage on the delimedand well-bated membranes, they have been converted successfully into cream coloured novelty leather. The leather wasfound fit to fabricate ladies hand bags,jewellery boxes, wallets, purses etc. The stomach leather was light weight (168-465 g) with adequate percent elongation at break (43.8 - 112. 3% longitudinally and 16 - 110% laterally) and hasshrinkage temperature between 73 - 77°e. The tensile strength of the leather (100.6 N/cm2-423 Nzcm? longitudinally and102.9 N/cm2-405 N/cm2Iaterally) was within the range of light weight fancy leathers. It bears good resistance to repeatedflexing (20,000 flexes, dry). Its has moderate resistance to washing in solution of neutral detergents. Thickness of theleather (0.6 - 1.3 mrn) is also suitable for making the fancy leather products.